2011
DOI: 10.5171/2011.726196
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Governance of Information Security in Banking System

Abstract: As modern banking increasingly relies on the internet and computer technologies to operate their businesses and market interactions, the threats and security breaches are highly increase in recent years. Insider and outsider attacks have caused global businesses lost trillions of Dollars a year. Therefore, that is a need for a proper framework to govern the information security in banking system. This paper highlights the information assets and potential threats for banking system. It further examines and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The integration of IT standards and best practices has many benefits. The primary one is the enabling of features that would be unavailable through the use of practices individually, leading to a more comprehensive and efficient approach [28,29]. Hence the need for an integrated solution to consolidate the best combination of IT standards and their best practices.…”
Section: It Governance It Framework and Digitalmentioning
confidence: 99%
“…The integration of IT standards and best practices has many benefits. The primary one is the enabling of features that would be unavailable through the use of practices individually, leading to a more comprehensive and efficient approach [28,29]. Hence the need for an integrated solution to consolidate the best combination of IT standards and their best practices.…”
Section: It Governance It Framework and Digitalmentioning
confidence: 99%
“…The threats facing the banking sector are evolving rapidly; just five years ago cyber-attacks were not recognised as a primary threat but just one of many. Ula et al (2011) identified the following threats: physical destruction of premises and systems by natural disasters; unintentional damage due to human error; abuse of system and sensitive information by employees or agents of the bank; systematic collection of sensitive information by foreign intelligence services; and external attacks which compromise confidentiality, integrity and availability of information. …”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, a bank which fails to protect its information systems not only loses its competitive advantage but also threatens its existence (Von Solms et al , 2011). Ultimately, the success of a bank can depend on its ability to manage its information security and provide secure services (Ula et al , 2011), and it is hardly surprising, therefore, that 80 per cent of leaders in the financial services sector cite cyber risks as a top concern (Travelers, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of threats to the financial institutions' economic security increases from year to year; their new, non-traditional forms and types that require the development of innovative approaches to counteract them appear ( Johnson, 2015;Amadae, 2017;Nelson, 2007). To prevent some of them, financial institutions needed to take comprehensive measures and to create security systems, for example, an information security system (Bank of Japan, 2000, Ula, Ismail, & Sidek, 2011. However, the protective effect would be more prominent in the context of creating a comprehensive economic security system of the financial institution, while one of those components would become the subsystem of information security.…”
Section: Introductionmentioning
confidence: 99%